Requirements Engineering: Foundation for Software Quality: 13th International Working Conference, REFSQ 2007, Trondheim, Norway, June 11-12, 2007. Proceedings - Sawyer, Pete; Paech, Barbara (Lecture notes in computer science, 2007)
REFSQ 2007 International Working Conference on Requirements Engineering: Foundation for Software Quality -- Comparing Goal Modelling Languages: An Experiment -- Automatically Generating Requirements from i* Models: Experiences with a Complex Airport Operations System -- Structuring the Co-design of Requirements and Architecture -- A Template for Requirement Elicitation of Dependable Product Lines -- A Flexible Requirements Analysis Approach for Software Product Lines -- Integrated Requirement Selection and Scheduling for the Release Planning of a Software Product -- A Value-Based Approach in Requirements Engineering: Explaining Some of the Fundamental Concepts -- Value-Based Requirements Engineering for Value Webs -- A Quantitative Assessment of Requirements Engineering Publications – 1963–2006 -- Handshaking Between Software Projects and Stakeholders Using Implementation Proposals -- Generating Fast Feedback in Requirements Elicitation -- Informing the Specification of a Large-Scale Socio-technical System with Models of Human Activity -- Integration Use Cases – An Applied UML Technique for Modeling Functional Requirements in Service Oriented Architecture -- Optimal-Constraint Lexicons for Requirements Specifications -- Integrating All Stages of Information Systems Development by Means of Natural Language Processing -- Information Flow Between Requirement Artifacts. Results of an Empirical Study -- Imperfect Requirements in Software Development -- Towards a Tomographic Framework for Structured Observation of Communicative Behaviour in Hospital Wards -- A Quality Performance Model for Cost-Benefit Analysis of Non-functional Requirements Applied to the Mobile Handset Domain -- Security Requirements for Civil Aviation with UML and Goal Orientation -- Challenges for Requirements Engineering and Management in Software Product Line Development -- ElicitO: A Quality Ontology-Guided NFR Elicitation Tool -- Exploring the Characteristics of NFR Methods – A Dialogue About Two Approaches -- Defining Reference Models for Modelling Qualities: How Requirements Engineering Techniques Can Help -- Integrating an Improvement Model of Handling Capacity Requirements with the OpenUP/Basic Process -- Mal-Activity Diagrams for Capturing Attacks on Business Processes -- Towards Feature-Oriented Specification and Development with Event-B.
Keywords: Konferenzschrift -- 2007 -- Trondheim; Qualitätssicherung; Softwareprodukt; Requirements engineering